A regulação do setor elétrico brasileiro como ferramenta de fomento para o desenvolvimento energético sustentável. - Camelo, Bradson Tiberio Luna (2014)
The modern way of life requires a continuous increase in energy use, to the sphere of production or to the consumption, but it has a great impact on the environment due to pollution generated by energy production. Thus, the regulation of the energy sector should consider one trilemma involving low costs, energy security (continuity and independence) and environmental preservation. In this line, this study aims to determine the level of regulatory importance of the principle of environmental protection established in the constitutional chapter of economic order, through the Program of Incentives for Alternative Electricity Energy Sources (PROINFA), for this it was studied most theories of regulation and the economics tools used in the international arena to stimulate alternative energy sources. To facilitate a strategic analysis, game theory has been used to integrate international and domestic relations in regulating the electricity sector. Thus, it was concluded that the Brazilian regulatory model does not prioritize environmental preservation, but it is a good choice to solve the games of energy, stimulating a sustainable energy matrix.